Detraining Effect on Pulmonary and Cardiovascular Autonomic Function and Functional Outcomes in Patients With Parkinson's Disease After Respiratory Muscle Training: An 18-Month Follow-Up Study - Huang, Chih-Cheng; Lai, Yun-Ru; Wu, Fu-An; Kuo, Nai-Ying; Cheng, Ben-Chung; Tsai, Nai-Wen; Kung, Chia-Te; Chiang, Yi-Fang; Lu, Cheng-Hsien (Frontiers in Neurology, 2021)
Background: The effect of 3-month respiratory muscle training (RMT) on pulmonary and autonomic function and functional outcomes has been demonstrated in patients with Parkinson's disease (PD); however, there is a paucity of information on the durability of the training effect. In this study, we monitored the pulmonary and cardiovascular autonomic function and clinical severity scales until 18 months after the cessation of RMT to elucidate the detraining effect after RMT. Methods: All patients with PD receiving RMT were assessed with clinical severity scales as well as pulmonary and autonomic function tests at four different stages (baseline on enrollment, immediately after 3 months of RMT, and 6 and 18 months after cessation of RMT). A control group of PD patients who did not receive RMT was also recruited for comparison. Pulmonary function parameters, including forced vital capacity (FVC), forced expiratory volume in one second (FEV1), maximum inspiratory pressure (MIP), and maximum expiratory pressure (MEP), were assessed. Cardiovascular autonomic function was assessed using measures including heart rate response to deep breathing (HRDB), Valsalva ratio, and baroreflex sensitivity. Clinical severity scores were also measured using the Hoehn and Yahr staging and the Unified Parkinson's Disease Rating Scale (UPDRS). Results: The results showed significant improvements in MIP, MEP, HRDB, and UPDRS immediately after RMT. Despite some decay, the improvements in pulmonary function (MIP and MEP) and functional outcomes (UPDRS) remained significant until 6 months of detraining (9 months after enrollment). However, the improvement in cardiovascular autonomic function (HRDB) was reversed after 6 months of detraining. Conclusions: Based on these findings, we recommend that RMT may be repeated after at least 6 months after previous session (9 months after enrollment) for patients with PD to maintain optimal therapeutic effects.